2022
DOI: 10.1186/s12939-022-01664-x
|View full text |Cite
|
Sign up to set email alerts
|

The true costs of cesarean delivery for patients in rural Rwanda: Accounting for post-discharge expenses in estimated health expenditures

Abstract: Introduction While it is recognized that there are costs associated with postoperative patient follow-up, risk assessments of catastrophic health expenditures (CHEs) due to surgery in sub-Saharan Africa rarely include expenses after discharge. We describe patient-level costs for cesarean section (c-section) and follow-up care up to postoperative day (POD) 30 and evaluate the contribution of follow-up to CHEs in rural Rwanda. Methods We interviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Various studies have suggested that financial constraints in the developing world contribute to the unavailability of many healthcare interventions, including CD [38]. Given that CD is one of the most expensive healthcare interventions in Rwanda, it is possible that women from wealthier families have better financial access than their counterparts from resource‐limited families in this study context [39]. In the same way, this study found a link between emergency cesarean delivery and women saying they had trouble paying for medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have suggested that financial constraints in the developing world contribute to the unavailability of many healthcare interventions, including CD [38]. Given that CD is one of the most expensive healthcare interventions in Rwanda, it is possible that women from wealthier families have better financial access than their counterparts from resource‐limited families in this study context [39]. In the same way, this study found a link between emergency cesarean delivery and women saying they had trouble paying for medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Developing strategies to improve the functional recovery for women after c-section could thus have substantial impact on improving physical and emotional wellbeing for families in the postpartum period, as well as potentially mitigate the financial impact of childbirth by c-section on families. Indeed in this same cohort we have previously reported that 6.4% and 27% of women experienced impoverishing and catastrophic expenditures, respectively due to hospital expenses alone, without consideration of the impact of lost economic productivity [ 59 ]. Both upstream and downstream strategies should be considered to help aid in the return to normal functional during the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…All interviewed patients had Rwanda's community-based health insurance, and described travel costs that were consistently higher than medical expenditures; this nding is consistent with other studies showing that non-medical costs pose barriers to care in LMICs even when medical costs are minimized. [32][33][34] Average monthly income in rural areas of Rwanda is about $27 USD; for farmers it is about $19 USD. [35] Repeated hospital visits consumed a signi cant portion of that income.…”
Section: Discussionmentioning
confidence: 99%